VD_FINDINFO HC / 2023 / 865 vom 26. Februar 2024 - VD Tribunal cantonal (2024)
SERVITUDE FONCIÈRE, ROUTE PRIVÉE, ASSAINISSEMENTEN GÉNÉRAL, RÉPARTITION DES FRAIS | 741 CC, 55 CPC (CH), 58 al. 1 CPC (CH), 84 CPC (CH)